LADY SUSAN VERNON: THE REPRESENTATION OF AN INDEPENDENT WOMAN IN A PATRIARCHAL SOCIETY IN JANE AUSTEN’S LADY SUSAN - Tesalonika Patras; Isnawati Lydia Wantasen; Arter Jodi Senduk (Universitas Sam Ratulangi, 2025)
Female representation in literature reflects not only artistic imagination but also cultural ideologies about gender and power. This study aims to analyze the concept and portrayal of an independent woman in a patriarchal society through the character Lady Susan Vernon in Jane Austen’s epistolary novel Lady Susan (1794, published posthumously in 1871). This qualitative research employs a feminist literary approach supported by two theoretical frameworks: Simone de Beauvoir’s existentialist feminism, as presented in The Second Sex (1949), and Robert Stanton’s theory of character and characterization, as discussed in An Introduction to Fiction (1965). De Beauvoir’s notion of “woman as the other” and her idea of female autonomy emphasize women’s capacity for self-determination and existential freedom beyond patriarchal constraints. Stanton’s theory, on the other hand, assists in examining Lady Susan as a round and multidimensional character revealed through her actions, dialogues, and the perspectives of other characters. The findings show that Lady Susan challenges traditional femininity through intelligence, manipulation, and rhetorical skill traits that enable her to exert informal power within a male dominated society. Although her methods are morally ambiguous, Lady Susan exemplifies nonconformist female independence and resistance to patriarchal norms. This study concludes that Jane Austen subtly critiques patriarchal limitations by presenting a female protagonist who actively negotiates social boundaries to assert her agency and autonomy. The research is limited to textual analysis of the novel and does not include comparative or historical reception studies; thus, the results should be interpreted within the chosen theoretical frameworks.